2014
DOI: 10.1039/c4ra07364a
|View full text |Cite
|
Sign up to set email alerts
|

Two novel oxovanadium–organophosphonate hybrids with a 3D supramolecular structure: synthesis, crystal structures, surface photovoltage and luminescent properties

Abstract: Two novel oxovanadium–organophosphonates with a 3D supramolecular structure, [{M(1,10–phen)}(VO)(OH)(hedp)]·H2O (M = Cu (1), Zn (2)), have been hydrothermally synthesized. The surface photovoltage and luminescent properties of the two compounds have been studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…All of them are constructed by sulfates, and thus the influence of the anion can be neglected. Compared with the syntheses and structures of 1 – 3 , it could be indicated that the dosage of structure-directing agents as well as the temperature play remarkable roles in the formation of zinc diphosphonates. , Compound 1 shows a 1D double chain constructed from Zn centers, HEDP ligands, and H 2 BAPEN molecules, in which HEDP displays two kinds of μ 3 -connection modes. The neighboring Zn···Zn distance separated by μ 3 -HEDP is 3.903(9) to 6.028(2) Å.…”
Section: Results and Discussionmentioning
confidence: 99%
“…All of them are constructed by sulfates, and thus the influence of the anion can be neglected. Compared with the syntheses and structures of 1 – 3 , it could be indicated that the dosage of structure-directing agents as well as the temperature play remarkable roles in the formation of zinc diphosphonates. , Compound 1 shows a 1D double chain constructed from Zn centers, HEDP ligands, and H 2 BAPEN molecules, in which HEDP displays two kinds of μ 3 -connection modes. The neighboring Zn···Zn distance separated by μ 3 -HEDP is 3.903(9) to 6.028(2) Å.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Organic crystals have been investigated widely for several decades on account of their potential applications in luminescent materials, photoelectric transformation, photothermal conversion, biological imaging, , and pharmaceutical preparations. , Particularly, the increasingly maturity X-ray diffraction (XRD) technology enables people to have intimate knowledge about crystals, so as to better gain certain functional materials through crystal design. Moreover, cocrystal molecules obtained through simple self-assembly often have some specific properties that monomolecular crystals do not have. In particular, some systems with strong intermolecular charge transfer (CT) between the electron donor and electron acceptor in solution have been studied and reported a lot. However, the electronic interactions between the donor and acceptor for the cocrystals are not deeply explored.…”
Section: Introductionmentioning
confidence: 99%
“…Continuous efforts have been made for synthesis of metal phosphonates, as one can expect a variety of interesting structures by multiple coordination sites and possible functionalities. Even though few organophosphonate structures are reported, the investigations of amine-templated metal organaphosphonates are just beginning, which may evolve into a rich structural variety. We have taken 1-hydroxyethane-1,1-diphosphonic acid (hedpH4) as the diphosphonate ligand to build a new family of open-framework structures with templated aliphatic amines. Our efforts yielded two new two-dimensional layer structures and one three-dimensional structure, namely, [H2DAP]­[Zn 6 (Hhedp) 2 (hedp) 2 ]·4H 2 O, I , [H2DAB]­[Zn 6 (Hhedp) 2 (hedp) 2 ]·4H 2 O, II , and [H2DAB]­[Zn 3 (hedp) 2 ]·2H 2 O, III .…”
mentioning
confidence: 99%